Morphology and Mechanical Properties of Polyamide 6/Polystyrene Blends Prepared by Diffusion and Subsequent Polymerization of Styrene in Polyamide 6 Pellets - Tan, Yin-Le (Materials (Basel), 2018)
Polyamide 6 (PA6)/polystyrene (PS) blend pellets were prepared by diffusion and subsequent polymerization of styrene in commercial PA6 pellets and processed into cuboid-shaped bars by injection molding. The average PS particle size in the bars was 240 nm, slightly higher than that in the blend pellets (120 nm), showing that only limited coalescence occurs during injection molding. The mechanical properties of PA6/PS bars were investigated by tensile, flexural, and notched impact tests. A 41% increase in notched impact strength was found without decreasing the modulus, tensile, and flexural strengths and elongation to break, when compared with those of neat PA6 bars. These good mechanical properties were attributed to the small PS particle sizes, and the good interfacial adhesion between PS particles and the PA6 matrix resulted from the occurrence of PS grafting onto PA6 during the preparation of the blend pellets and injection molding. The water sorption and water-induced dimensional changes in PA6/PS bars were significantly less than those of neat PA6 bars because of the presence of the hydrophobic PS phase. This work reveals that the PA6/PS quasi-nanoblend pellets are useful stock for plastic production.